Analisis Strategi Reformasi Administrasi Pelayanan Publik Melalui SIAK di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Aceh Barat - Salsabila, Salsabila; Fadhly, Zuhrizal; Husna, Cut Asmaul (Journal of Administration, Governance, and Political Issues, 2024)
Administrative reform is an increase in the ability of bureaucrats to be able to make normative policies a reality in the field. This research aims to analyze how the service reform strategy is implemented at the West Aceh District Dukcapil Office through the online-based SIAK Population Administration Information System (Population Administration Information System). Apart from that, in its implementation there are also several weaknesses and obstacles faced. The service renewal program which is the main focus in this research, namely using the SIAK system in West Aceh District, is studied in depth. The method used in this research is descriptive qualitative research and data analysis using observation, interviews, and documentation. As well as data analysis techniques using data reduction, presentation of data and conclusions. This is measured from the 2019 Wijaya theory using 4 indicators, namely Value Transformation, Organizational Arrangement and Work Procedures, Management System Strengthening, and Increasing HR Competency. The results of this research are that, the SIAK system in West Aceh has been implemented, However, its implementation is not yet optimal because it cannot reach the community as a whole.